'Y' feel me?' How do we understand the person with dementia?. (May 2013) - Hughes, Julian C
As dementia progresses problems of understanding emerge. Eventually spoken language can be lost. And yet, even into the severer stages of dementia, close carers can often understand the person in a variety of ways. Loss of language is not just a practical problem. It raises philosophical issues too. As Wittgenstein suggested, understanding entails grasping a form of life. Our understanding of agitated, pacing behaviour is similarly based on a unique history, on culture, on context. Hence, a philosophy gestures at the foundations of care. There is the potential to feel the person's meaning, even when it cannot be spoken. This is not simply by means of an alternative to language. The philosophy suggests that our engagement with the person is through and through. Understanding anyone is more like an aesthetic judgement than a cognitive act.